(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
The study included 303 women aged of 20 to 40 years with acne. Advanced survey included evaluation of endocrine profile and steroid profile of urine. A group of 31 women was allocated; this group was characterized by early-onset acne and hirsutism, android-type obesity, the prevalence of noninflammatory elements, seborrhea, disorders of endocrine profile and steroid profile of urine, metabolic disorders, increased adrenal glands, and lack of effectiveness of oral contraceptives. At the same time, specific clinical and laboratory signs were revealed that allows to assign them to the diagnostic criteria of adrenal hyperandrogenism in women with acne. It’s made it possible to select the rational effective treatment for these patients in the future.